KARAKALPAKSTAN MUSEMS IN THE CHRONICLE OF THE INDEPENDENCE YEARS - Khojaniyazov, U. (FAN va JAMIYAT, 2020)
The article the problems pertaining to the attention drawn to culture and spirituality of the nation during the years of Independence in the Respublic of Uzbekistan are considered. Museums occupy a significant role in the development of culture and spirituality of the nation. The tendance from the state’s side and the leadership of Uzbekistan in the development of museums during the years of Independence is expounded. Special attention is drawn to conditions of the museums in Karakalpakstan that are considered as a significant part of Uzbekistan, and to the issues of how they are evaluated by international experts. Therein, thorough information about the Art Museum named after I.V. Savitsky and museum of Regional Studies, that are located in Nukus city, is given in the article.